PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. ENGINEERING DI KOTA BEKASI - Dwi Astuti; Zahara Tussoleha Rony; Rycha Kuwara Sari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the influence of work discipline and work environment on employee work productivity at PT. Engineering in Bekasi City. The type of research used in this study is quantitative research. The sample technique uses a non-probability sampling technique, then the sample is taken using a type of convenience sampling, and the number of samples is determined by the hair formula, namely the number of indicators from each variable multiplied by 5 to 10, so in this study through the number of questionnaire indicators multiplied by 5, namely a total sample of 75 employees of PT. Engineering in Bekasi City. The method used in this test is using the Structural Equitation Model (SEM). The data was processed using SMART PLS 4.0. The results of this study show that (1) work discipline has a positive and significant effect on the performance of employees of PT. Engineering in Bekasi City, and (2) the work environment has a positive and significant effect on the performance of employees of PT. Engineering in Bekasi City.